Mechanism of Creating Happiness in Life: A Policy Evaluation of Smart City Development in DKI Jakarta - Anggraini, Dewi Yulia; Salomo, Roy Valiant (Syntax Corporation, 2023)
The smart city development policy carried out by the DKI Jakarta Provincial Government since 2014 aims to improve the quality of life. Theoretically, the achievement of improving the quality of life can be described through happiness indicators. Based on data from the Central Bureau of Statistics (BPS), the value and ranking of the happiness index for the civil of DKI Jakarta in 2021 are worse than the achievements in 2017. Therefore, this study aims to evaluate the mechanism for creating life happiness in the smart city of DKI Jakarta according to the characteristics of the Happiness Driven Smart City (HDSC). The data collection method is through document tracing and utilization of secondary data. The data analysis is carried out descriptively by using HDSC characteristics criteria. The study shows that the mechanism for creating happiness through developing a smart city by the government of DKI Jakarta is generally under the HDSC characteristic criteria. Therefore, the authors recommend several improvements to create a happy life in this city according to the HDSC characteristic criteria.